150k views
3 votes
Solve the system by substitution. x=-y-9 6x-5y=1

User Mja
by
5.2k points

2 Answers

1 vote

Answer:

x= -64, y= 55

Explanation:

x=-y-9

6(y-9)-5y=1

6y-54-5y=1

y=55

x=-55-9

x=-64

User Atgrubb
by
4.5k points
1 vote

Answer:

{x=-4

{x= -5

Explanation:

Substitute into one of the equations:6(- y -9) - 5y=1

Apply Multiplicative Distribution Law:- 6y-54-5y=1

Rearrange unknown terms to the left side of the equation:-6y -5y = 1+54

Combine like terms:- 11y= 1+54

Calculate the sum or difference:-11y=55

Divide both sides of the equation by the coefficient of variable:y= 55÷(-11)

Remove the parentheses:y = -55÷11

Calculate the product or quotient:y=-5

Substitute into one of the equations:x=-(-5)-9

Remove the parentheses:x=5-9

Calculate the sum or difference:x=-4

The solution of the system is:{x=-4

{x=-5.

User Bel
by
4.4k points